Dry spells in the brazilian "cerrados" region: frequency and probability of occurrence - Assad, Eduardo Delgado; Sano, Edson Eyji; Masutomo, Ryo; de Castro, Luis Hernan R.; da Silva, Fernando A. Macena (Pesquisa Agropecuaria Brasileira, 1993)
An analysis of daily precipitation data from 100 pluviometric stations in the Brazilian "cerrados" (savanna-like vegetation), using historical. series of 20 or more years, was utilized to identify dry spells of 10, 15 and 20 days. This information of the frequencial analysis was arranged using the Geographical Information System. The occurrence probability of dry spells, estimated by the distribution function of Gumbell & Weibull using recurrence intervals of 5 to 100 years, allowed identification of risk periods for conventional agriculture (nonirrigated). Therefore, it was possible to make a global analysis of this climatic problem, which is critical for the agricultural production in the Brazilian "cerrado" ecosystem.